Reassessing the link between firm size and exports - Pedro Jesús Hernández Martínez (Kiel Institute for the World Economy (IfW), 2016)
The small average size of Spanish firms has been put forward as the main impediment to their international competitiveness. This paper re-examines the link between firm size and exports. The new theories of international trade emphasize firm heterogeneity as the theoretical basis of export behavior. In the context of this heterogeneity, the paper uses the quantile regression methodology to analyze the effect of firm size on firm export propensity (percentage of exported sales). The paper confirms the existence of a positive relationship between firm size and export intensity but finds that the conventional estimates of the elasticity of export propensity with respect to firm size on the average of the export propensities distribution underestimate the effect at the bottom of the distribution and overestimate the effect on most of it. Consequently, policies aimed at increasing exports should concentrate their efforts on increasing the size of those firms with lower export propensity.
Keywords: F14; L25; 330; exports; firm size; quantile regression; firm heterogeneity